2019
DOI: 10.1088/1361-648x/ab18ef
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of negative electron affinity from light metals on the oxygen-terminated diamond (1 1 1) surface

Abstract: Recent computational work has shown that light metals adsorbed onto the oxygenated diamond (100) surface have the potential to give diamond a temperature-stable negative electron affinity (NEA). Here, we use density functional theory to study three of these metals, lithium, magnesium and aluminium, on the (111) surface. We show that all three of these metals adsorbed onto the ketone O-terminated diamond surface can possess a large NEA and adsorption energies above that of H-termination at monolayer (ML) or sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…The quality of the electron beam deposition was also proven by the appearance, after the 800 °C anneal, of a faint (2 × 1) LEED pattern on the (100) surface, as predicted by computational experiments. [ 35 ] The (111) surface showed a (1 × 1) LEED pattern, consistent with computational calculations that predicted this to be the most stable structure. [ 35 ]…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The quality of the electron beam deposition was also proven by the appearance, after the 800 °C anneal, of a faint (2 × 1) LEED pattern on the (100) surface, as predicted by computational experiments. [ 35 ] The (111) surface showed a (1 × 1) LEED pattern, consistent with computational calculations that predicted this to be the most stable structure. [ 35 ]…”
Section: Resultssupporting
confidence: 75%
“…The Al−O−diamond system has recently been studied computationally on both the (100) and (111) diamond surfaces. [ 33–35 ] Al adsorption onto O‐terminated diamond was predicted to give large adsorption energies (from −6.0 to −7.3 eV) on both (100) and (111) diamond at 0.25 ML Al coverage due to the strong ionic bond between Al and O, as well as NEA values as large as ≈−2.2 eV. However, at higher coverages, some AlAl metallic bonding occurs, making Al less ionic and the surfaces mostly of positive electron affinity (PEA).…”
Section: Introductionmentioning
confidence: 99%
“…However, H-terminated diamond surfaces suffer from the phenomena of water adsorption, leading to charge transfer and unnecessary band bending [23,24]. Along with the instability of H termination at higher temperatures (> 700 °C) [25], this restricts the use of H-terminated surface in thermionic applications. Cs-O-terminated diamond surface has been demonstrated to possess a work function of 1.5 eV, but Cs desorbs above a temperature of 400 °C [26].…”
Section: Introductionmentioning
confidence: 99%
“…Crystals 2019, 9, x FOR PEER REVIEW 2 of 11 diamond [24][25][26][27][28][29][30][31]. However, it still need systematically comparing of the impacts of different doping on the growth of CVD diamond films.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the CH 3 adsorption is one of the main growth steps of the diamond deposited, using the hot filament chemical vapor deposition (HFCVD) method under the H 2 and CH 4 atmosphere [22,23]. DFT calculation allows the better understanding of the influence of the impurities on the growth of diamond [24][25][26][27][28][29][30][31]. However, it still need systematically comparing of the impacts of different doping on the growth of CVD diamond films.…”
Section: Introductionmentioning
confidence: 99%